The Essential Role of Rac1 Glucosylation in Clostridioides difficile Toxin B-Induced Arrest of G1-S Transition - Petersen, Lara; Stroh, Svenja; Schöttelndreier, Dennis; Grassl, Guntram A.; Rottner, Klemens; Brakebusch, Cord; Fahrer, Jörg; Genth, Harald (Frontiers in Microbiology, 2022)
C. difficile infection (CDI) in humans causes pseudomembranous colitis (PMC), which is a severe pathology characterized by a loss of epithelial barrier function and massive colonic inflammation. PMC has been attributed to the action of two large protein toxins, Toxin A (TcdA) and Toxin B (TcdB). TcdA and TcdB mono-O-glucosylate and thereby inactivate a broad spectrum of Rho GTPases and (in the case of TcdA) also some Ras GTPases. Rho/Ras GTPases promote G1-S transition through activation of components of the ERK, AKT and WNT signalling pathways. With regard to CDI pathology, TcdB is regarded of being capable of inhibiting colonic stem cell proliferation and colonic regeneration, which is likely causative for PMC. In particular, it is still unclear, the glucosylation of which substrate Rho-GTPase is critical for TcdB-induced arrest of G1-S transition. Exploiting SV40-immortalized mouse embryonic fibroblasts (MEFs) with deleted Rho subtype GTPases, evidence is provided that Rac1 (not Cdc42) positively regulates Cyclin D1, an essential factor of G1-S transition. TcdB-catalyzed Rac1 glucosylation results in Cyclin D1 suppression and arrested G1-S transition in MEFs and in human colonic epithelial cells (HCEC), Remarkably, Rac1-/- MEFs are insensitive to TcdB-induced arrest of G1-S transition, suggesting that TcdB arrests G1-S transition in a Rac1 glucosylation-dependent manner. Finally, human intestinal organoids (HIOs) specifically expressed Cyclin D1 (neither Cyclin D2 nor Cyclin D3), which expression was suppressed upon TcdB treatment. From our finding in in HCEC and HIOs can be concluded that specifically Cyclin D1 expression seems to be regulated by Rho GTPases (most likely Rac1) and in turn seems to be susceptible to TcdB-induced suppression. With regard to PMC, toxin-catalyzed Rho GTPase glucosylation and subsequent G1-S arrest of colonic stem cells seems to be causative for decreased repair capacity of the colonic epithelium and delayed epithelial renewal.